Lansium Domesticum: In Vitro Antimalarial Bioactivity And Its Effect On Plasmodium Falciparum Gene Expression - Angela, Siner (Universiti Malaysia Sarawak (UNIMAS), 2013)
Reduced efficacies of current antimalarials meant that increasing the options for malaria chemotherapeutics continue to be an important part in global malaria control efforts. Lansium domesticum, a tree cultivated for its fruits, can be found ranging from China, Indochina to the Malay Archipelago. In Borneo, various parts of L. domesticum have been reported to be used by traditional healers for the treatment of malaria. The main objective of this study was to determine the mechanism of antiplasmodial activity of extracts prepared from the leaves of L. domesticum. The in vitro antiplasmodial activity of L. domesticum leaf extracts from two trees were extracted by two methods and assessed on two chloroquine-sensitive Plasmodium falciparum laboratory adapted clones 3D7 and HB3. This was done based on the parasite inhibition assay by the World Health Organisation. Leaves from Tree 1 were extracted using the organic solvent method, while leaves from Tree 2 were extracted using the organic solvent method and an ethno preparation based method. The organic solvent method resulted in the methanol extract and the dichloromethane (DCM) fraction; whereas the ethnopreparation-based methods resulted in the aqueous extracts. The methanol extracts derived from both trees in this study were active against P. falciparum clone 3D7 (IC50 of 84 μg/ml for Tree 1 and 28 μg/ml for Tree 2) and against P. falciparum clone HB3 (IC50 of 16 μg/ml for Tree 2). However, the malaria-active compounds appeared to partition into the DCM fraction (IC50 of 26 μg/ml for Tree 1 and 24 μg/ml for Tree 2). For the aqueous extracts, the hot and boiling water extracts were active against P. falciparum clone 3D7, whereas the cold water extract was active against P. falciparum clone HB3. However, the aqueous extracts were less potent compared to the organic solvent extracted samples.Therefore, the DCM fraction of L. domesticum leaf extracts was selected for studying the mechanism of activity on P. falciparum intraerythrocytic maturation. Gene expression profiles of P. falciparum clone 3D7 cultured in 10 μg/ml and 100 μg/ml of the DCM fraction over 4- or 12- hour period with non-treated cultures was compared using the GeneChipÒ Plasmodium/Anopheles genome array (AffymetrixÔ) and analysed using GeneSpringÒ (Agilent). Preliminary analysis using the one-on-one approach, comparing non-treated with treated parasites for a 4- or 12-hour period, was inconclusive. A multivariate analysis by Dr. Ken Laing showed that 12-hour exposure to the 100 μg/ml DCM fraction of L. domesticum was significantly different from non-treated cultures. Functional characterisation of this output using the Database for Annotation, Visualisation and Integrated Discovery (D.A.V.I.D.) suggests that 12-hour exposure to the 100 μg/ml DCM fraction of L. domesticum appears to target genes associated with the mitochondrion. Although this could be a reflection of a general downstream response to treatment rather than the specific mode of action of L. domesticum activity, identification of down-regulated genes that included oxidative phosphorylation, citrate cycle (TCA cycle), folate biosynthesis, purine/pyrimidine metabolism, nitrogen metabolism, fatty acid metabolism and ubiquitin-mediated proteolysis, supports the mitochondrion as the possible target. On the other hand, up-regulation of genes for ribosome, spliceosome, oxidative phosphorylation, fatty acid metabolism, purine metabolism, pentose phosphate pathway, fructose and mannose metabolism may be a reflection of secondary downstream compensation for the inhibitory effects of the DCM fraction of L. domesticum. Therefore, the DCM fraction of L. domesticum needs to be further assessed and studied as a potential addition to the antiplasmodial drug arsenal to help in the fight against malaria.